1976
DOI: 10.1007/bf01181577
|View full text |Cite
|
Sign up to set email alerts
|

The ultrastructure of the sheath around chronically implanted electrodes in brain

Abstract: Insulated, bipolar stainless steel electrodes were chronically implanted in various regions of the cat brain and the long-term structural changes in the tissue surrounding the electrodes were studied by light and electron microscopy. A sheath surrounded and separated the electrode from normal grey or white matter. A layer of foreign body giant cells of variable thickness was formed adjacent to the electrode. This layer was attenuated in some places so that it was unrecognizable by light microscopy. The bulk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 33 publications
3
37
2
Order By: Relevance
“…In particular, by 4 weeks following implantation, the reaction has a stereotypical organization consisting of hypertrophic astrocytes, fibroblasts, and meningeal cells [10][11][12][13][14][15][16][17][18][19][20][21][22][23] that surrounds an activated macrophage/microglial/ foreign body giant cell core found immediately adjacent to the implant [15,17,22]. Within this region of reactive gliosis, numerous studies have described a decrease in the neuronal population [10][11][12][13]15,[20][21][22][23][24]. Quantitative studies have shown that the response is limited to the immediate vicinity of the electrode extending a few hundred microns from the interface into surrounding brain tissue [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, by 4 weeks following implantation, the reaction has a stereotypical organization consisting of hypertrophic astrocytes, fibroblasts, and meningeal cells [10][11][12][13][14][15][16][17][18][19][20][21][22][23] that surrounds an activated macrophage/microglial/ foreign body giant cell core found immediately adjacent to the implant [15,17,22]. Within this region of reactive gliosis, numerous studies have described a decrease in the neuronal population [10][11][12][13]15,[20][21][22][23][24]. Quantitative studies have shown that the response is limited to the immediate vicinity of the electrode extending a few hundred microns from the interface into surrounding brain tissue [13,15].…”
Section: Introductionmentioning
confidence: 99%
“…From our observations as well as those of others (Collias & Manuelidis, 1957, Schultz & Willey, 1976, it is evident that implantation of electrodes elicits a tissue response which is definable, reproducibly limited as to involvement, and divided into developmental stages. Although the degree of involvement between traumatic, hemodynamic, and cytotoxic factors remains unclarified, the net effect is definable in tissue response and should not be ignored in conclusions drawn from studies involving implantation.…”
Section: Le Journal Canadien Des Sciences Neuroiogiquesmentioning
confidence: 67%
“…A border zone at the electrode/parenchymal interface was composed of a mixture of hemorrhagic, fibrous, phagocytic, and necrotic elements. A clearly defined sheath of a cellular lining as was reported in a study following 30 days chronic implantation (Schultz and Willey, 1976) had not developed in these animals. In the present studies no detectable capillary proliferation was encountered in border zone.…”
Section: Le Journal Canadien Des Sciences Neuroiogiquesmentioning
confidence: 83%
See 2 more Smart Citations